2015
DOI: 10.3390/jcm4061325
|View full text |Cite
|
Sign up to set email alerts
|

Horizon 2020 in Diabetic Kidney Disease: The Clinical Trial Pipeline for Add-On Therapies on Top of Renin Angiotensin System Blockade

Abstract: Diabetic kidney disease is the most frequent cause of end-stage renal disease. This implies failure of current therapeutic approaches based on renin-angiotensin system (RAS) blockade. Recent phase 3 clinical trials of paricalcitol in early diabetic kidney disease and bardoxolone methyl in advanced diabetic kidney disease failed to meet the primary endpoint or terminated on safety concerns, respectively. However, various novel strategies are undergoing phase 2 and 3 randomized controlled trials targeting inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 102 publications
0
29
0
1
Order By: Relevance
“…Despite side effects, results of clinical trials continue to show therapeutic benefits of MR antagonists in a growing list of conditions 2, 96, 116, 117 , clearly indicating the need for better MR antagonists 59, 75, 118120 . The Dialysis Outcomes Heart Failure Aldactone Study and others have been demonstrated their utility in stemming the progression of chronic kidney disease 121123 . Another is the dramatic discovery that central serous chorioretinopathy, a rapidly progressing and heretofore untreatable cause of permanent destruction of the retina, is reversed by spironolactone and eplerenone 124, 125 .…”
Section: The First Generation Antagonistsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite side effects, results of clinical trials continue to show therapeutic benefits of MR antagonists in a growing list of conditions 2, 96, 116, 117 , clearly indicating the need for better MR antagonists 59, 75, 118120 . The Dialysis Outcomes Heart Failure Aldactone Study and others have been demonstrated their utility in stemming the progression of chronic kidney disease 121123 . Another is the dramatic discovery that central serous chorioretinopathy, a rapidly progressing and heretofore untreatable cause of permanent destruction of the retina, is reversed by spironolactone and eplerenone 124, 125 .…”
Section: The First Generation Antagonistsmentioning
confidence: 99%
“…Two in early stages of clinical testing in patients with hypertension and diabetic nephropathy is MT-3995 (Mitsubishi) and SC-3150 (Daiichi-Sankyo) 123, 140, 155 . Phase II clinical trials have been completed for LY2623091 (Eli Lilly) was compared to a placebo and spironolactone in patients with primary hypertension (NCT02194465) and to eplerenone, but not a placebo, in men and women with chronic renal disease (NCT01427972).…”
Section: Other Potential Mr Antagonistsmentioning
confidence: 99%
“…Unfortunately, RAAS inhibitor trials have also produced some disappointing results, including the failure of primary prevention studies (The Renin Angiotensin System Study [RASS]), and serious side effects observed with dual RAAS blockade 2 . The lack of complete protection against the development of complications with traditional RAAS inhibitors underscores the need for new therapeutic strategies.…”
Section: Renal Protective Therapies Targeting Neurohormonal Activationmentioning
confidence: 99%
“…Unfortunately, recent renal protection trials have either failed, demonstrated harm or reported effects that are far below expectations based on data from experimental models. For example, within the last 5 years, trials with early renin-angiotensin-aldosterone system (RAAS) blockade in patients with type 1 (T1D) and type 2 diabetes (T2D), with dual RAAS blockade, protein kinase C-beta inhibition, endothelin receptor antagonists and the anti-oxidant bardoxolone have reported disappointing results 2 . Accordingly, this review will summarize promising novel therapies that may slow the progression of DN by targeting pathogenic mechanisms such as neurohormonal activation, tubuloglomerular feedback and renal inflammation/fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…It inhibits the production of thromboxane A2 and is used as anti-platelet agent instead of aspirin [190] . Experimental studies showed Sarpogrelate effect on mesangial type Ⅳ collagen production, on albuminuria in DKD, on antibody-mediated glomerular injury and on nephrotoxin-induced kidney fibrosis [191] . A clinical trial showed a significant decrease of urine albumin excretion in diabetic kidney disease after addition of Sarpogrelate [192] .…”
Section: Sharaf El Din Uaa Et Al Stop Chronic Kidney Disease Progrementioning
confidence: 99%